Stochastic processes for pulsar timing noise: fluctuations in the internal and external torques. Issue 2 (27th January 2023) - Antonelli, Marco; Basu, Avishek; Haskell, Brynmor
Abstract: Young pulsars deviate from a perfectly regular spin-down by two non-deterministic phenomena: impulsive glitches and timing noise. Both phenomena are interesting per se and may provide insights into the superfluid properties of neutron stars, but they also act as a barrier to high-precision pulsar timing and gravitational wave experiments. We study a minimal stochastic model to describe the spin-down of a multicomponent neutron star, with fluctuations in both the internal and external torques. The power spectral density and timing noise strength of this kind of model can be obtained analytically and compared with known results from pulsar timing observational campaigns. In particular, the presence of flat regions of the power spectral density can be interpreted as a signature of the presence of internal superfluid components. We also derive the expected scaling of the timing noise strength with the pulsar's rotational parameters (or characteristic age). Therefore, the present framework offers a theoretical guideline to interpret the observed features of timing noise in both single pulsars and across the pulsar population.